Competition, risk-shifting, and public bail-out policies - Reint E. Gropp; Hendrik Hakenes; Isabel Schnabel (Max Planck Institute for Research on Collective Goods, 2010)
This paper empirically investigates the effect of government bail-out policies on banks outside the safety net. We construct a measure of bail-out perceptions by using rating information. From there, we construct the market shares of insured competitor banks for any given bank, and analyze the impact of this variable on banks' risk-taking behavior, using a large sample of banks from OECD countries. Our results suggest that government guarantees strongly increase the risk-taking of competitor banks. In contrast, there is no evidence that public guarantees increase the protected banks' risk-taking, except for banks that have outright public ownership. These results have important implications for the effects of the recent wave of bank bail-outs on banks' risk-taking behavior.
Keywords: G21; G28; L53; 330; Government bail-out; implicit and explicit government guarantees; banking competition; risk-taking